“Deconstructing” the northern levantine palace: genesis and development of a public building - Iamoni, Marco ca. 20./21. Jh. (Ägypten und Levante, 2019)
Palaces, in many respects, represent the main outcome of the great socio-economic transformation that characterised the outgrowth of urban societies during the first half of the second millennium BC. In the Levant, the type of building that appeared was characterised by traits that make it quite different from similar and contemporaneous buildings located in Mesopotamia. This fact suggests the existence of an independent local tradition in the Levant which has thus usually been analysed in distinct chronological segments, with separate discussions of the relevant Middle Bronze Age (MBA) and Late Bronze Age (LBA) evidence to hand. This work uses two case studies of palace architecture dating to the MBA and LBA from Qatna to propose an analysis that highlights the existence of several shared traits. Via comparisons with contemporary examples, in particular Alalakh, a common genesis that developed along a unique and continuous path is suggested for both MBA and LBA palaces. The social role of northern Levantine palaces is thus seen as an expression of new local leaderships and as the vehicle of a common language whose origin might be traced back to the emergence of the so-called Amorite Koiné.